Shape Characterization for Optimisation of Bra Cup Moulding (Journal of Fiber Bioengineering and Informatics, 2018)
Foam cup moulding of seamless and traceless undergarments is an important manufacturing techniquefor the intimate apparel industry. Nevertheless, there is limited knowledge about the optimizationof the main moulding parameters. In this study, Response Surface Methodology (RSM), based ona Box-Behnken Design (BBD), was used to analyze the effects of the three main moulding factors(moulding temperature, dwell time and size of mould head) on the shape conformity of moulded bracups and formulate a prediction model in a second-order polynomial form. Design and analysis ofexperimental data were carried out by the Minitab R15.1.30.0. The analyses revealed that mouldingtemperature greatly affected the shape conformity of moulded bra cup, and the interactions betweenmoulding temperature and dwell time have major influence on the control of bra cup moulding process.The optimal cup shape conformity and the corresponding settings of the selected variables in bra cupmoulding process were obtained by solving the quadratic regression model, as well as by analyzing theresponse surface contour plots. When moulding temperature and dwell time were set as 200° and 140s fora mould head size of 36C, the optimum shape conformity of the moulded bra cup was predicted as 83%.The adopted model was proved reasonably and effectively. This research provided a reference for theintimate apparel manufacturers to improve the control of the bra cup molding process and productionefficiency.